Cross-Section Observational Study to Assess Antimicrobial Resistance Prevalence among Bovine Respiratory Disease Bacterial Isolates from Commercial US Feedlots - Erin Jobman; Jacob Hagenmaier; Nathan Meyer; Lee Bob Harper; Lisa Taylor; Kip Lukasiewicz; Dan Thomson; James Lowe; Shane Terrell (MDPI AG, 2023)
Antimicrobial resistance (AMR) is a global public health threat that jeopardizes efficacy of antibiotics in veterinary and human medicine. Antibiotics are commonly administered to target the bacterial component of bovine respiratory disease (BRD). The objectives of this study were to obtain a better understanding of antibiotic resistance in BRD-associated bacteria (Mannheimia haemolytica, Pasteurella multocida, and Histophilus somni), investigate the clinical significance of AMR by monitoring clinical outcomes, and determine if regional differences exist in AMR trends. Deep pharyngeal swabs were used to sample beef cattle at initial BRD diagnosis (n = 453) from US feedlots representing three geographic regions. Organisms were identified by bacterial culture and subjected to broth microdilution antimicrobial susceptibility testing. Bacterium prevalence include P. multocida (36.0%), M. haemolytica (32.7%), and H. somni (28.5%). Of the Histophilus isolates, 39.5% were resistant to at least one antimicrobial, compared to 11.7% and 8.8% Pasteurella and Mannheimia, respectively. Non-susceptibility across all organisms was 5.7 X more likely in animals that received metaphylaxis, than those that did not (p < 0.0001; OR 5.7; CI 2.6-12.5). During days on feed 21-40, non-susceptibility of Histophilus was 8.7 X more likely than Mannheimia (p = 0.0002; OR 8.7; CI 2.8 to 27.4) and 6 X more likely than Pasteurella (p = 0.0016; OR 6.0; CI 2.0-18.0).